Comparison of pulmonary veins in patients with and without atrial fibrillation using multidedector computed tomographic angiography - Akdur, Pınar; Türkvatan, Aysel (The European Research Journal, 2022)
Objectives: Atrial fibrilation (AF) develops from an arrhythmogenic ectopic focus, which triggers the vicious circle that creates arrhythmias. Arrhythmogenic foci are often located in the transition areas between the pulmonary veins and the left atrial endothelium. This study aims to compare the pulmonary vein anatomy of patients with and without AF using multidetector computed tomographic (MDCT) angiography and to evaluate the relationship between the presence of pulmonary vein variations and the development of AF. Methods: Seventy cases (38 males, 32 females) aged between 23 and 75 (mean age: 49.9 ± 13.3 years) were included in this study. This study consisted of 20 patients undergoing endovascular radiofrequency catheter ablation with AF and 50 participants (control) without AF. MDCT angiography examination was performed for the evaluation of pulmonary vein anatomy and variations. Results: Normal pulmonary vein anatomy was observed in 30% (n = 6) of the study group, 60% (n = 30) of the control group, and 51.4% (n = 36) of the total of both groups. Variation in pulmonary vein anatomy (accessory pulmonary vein or common ostium) was detected in 48.6% (n = 34/70) of the cases. The most common variation was the presence of accessory pulmonary vein (35.7%). Common ostium was found to be the second most common variation (12.8%). All common ostia were localized on the left side. Early branching of pulmonary veins was detected in 41 (58.5%) of 70 cases. Conclusions: Accesory pulmonary vein, common ostium and early branching are more frequently present in patients with AF.